The relationship of graft survival and herpes simplex virus latency in recipient corneal buttons - Aydemir, Orhan; Turkcuoglu, Peykan; Bulut, Yasemin; Kalkan, Ahmet (Dove Medical Press Ltd, 2007)
Purpose: To demonstrate relationship between herpes simplex virus (HSV) corneal latency and graft survival. Methods: Prospective case control study. 28 recipient corneal buttons and donor cornea-scleral remnants were examined for HSV DNA with polymerase chain reaction (PCR). None of the recipient had a history of HSV infection. Serum samples of graft recipients were analyzed for the presence of anti-HSV IgG and IgM with enzyme-linked immunosorbent assay technique. All corneas were free of stromal scarring or epithelial defect before sampling and had an endothelial cell density of >2000 cells/mm(2). Results: In twenty three patients (82%) anti-HSV IgG was detected in serum. In none of the recipients anti-HSV IgM was positive. HSV DNA was positive in six out of twenty eight (21%) of the recipient corneal buttons and none of the donor cornea-scleral remnants. In eighteen-months follow-up period three out of six (50%) HSV DNA positive and one out of twenty-two (4.5%) HSV DNA negative patients experienced late endothelial failure that was statistically significantly different (p = 0.022). Conclusion: Even without a history of HSV keratitis, presence of latent HSV virus in recipient cornea is an important risk factor for subsequent graft survival.
Keywords: herpes simplex virus; polymerase chain reaction; corneal latency; corneal graft survival